A History of the Akropolis of Athens - Miller, Walter (Gorgias Press, 2009)
This paper presents a thorough review of the physical remains and excavation history of the Athenian Acropolis from the Bronze Age to the early 20th Century
Description based on online resource; title from PDF title page (publisher's Web site, viewed 10. Jan 2022)
Keywords: HISTORY / General